1979
DOI: 10.2337/diab.28.5.479
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Desaturation in Experimental Diabetes Mellitus

Abstract: Microsomal fatty acid desaturation is defective in streptozotocin-induced experimental diabetes. This defect is correctable by insulin treatment. The electron transport chain needed for microsomal fatty acid desaturation was studied in liver microsomes of streptozotocin diabetic rats, and the defect was localized to the terminal desaturase enzyme. Cytochrome b5 levels were elevated in the face of decreased fatty acid desaturation and returned to normal after 48 h of insulin treatment; 2 U of regular insulin ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 4 publications
2
24
0
1
Order By: Relevance
“…Insulin plays an important role in desaturation. Insulin treatment in humans (Tilvis et al 1986;el Boustani et al 1989) as well as experimental diabetic animals (Gellhorn and Benjamin 1964;Eck et al 1979;Prasad and Joshi 1979) stimulates desaturases. Eck et al (1979) reported that Table II.…”
Section: Desaturation and Elongationmentioning
confidence: 98%
“…Insulin plays an important role in desaturation. Insulin treatment in humans (Tilvis et al 1986;el Boustani et al 1989) as well as experimental diabetic animals (Gellhorn and Benjamin 1964;Eck et al 1979;Prasad and Joshi 1979) stimulates desaturases. Eck et al (1979) reported that Table II.…”
Section: Desaturation and Elongationmentioning
confidence: 98%
“…In experimental diabetes and in spontaneously diabetic rats, there are reduced activities of ⌬-9, ⌬-6, and ⌬-5 liver microsomal desaturases, which are restored after insulin treatment [65,66].…”
Section: Insulin Resistancementioning
confidence: 99%
“…Insulin is well known for its stimulatory effect on cell proliferation [22] particularly for keratinocytes [23,24]. Further, insulin will increase 14 C-acetate incorporation into polyunsaturated fatty acids of skin [25] and increase fatty acid desaturase activity [20]. Thus, the response observed in the permeability kinetics of the insulin-treated diabetic rats may be from a hyperproliferation response or a further lipid imbalance in the stratum corneum lamella.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the insulin is having an independent effect on the epidermis beyond the systemic regulation of carbohydrate metabolism. Potentially, the epidermis may have experienced an overexposure of insulin, as a long-acting form was used (protamine zinc) which was administered at a relatively high dose [20]. Consequently, skin insulin levels may have been very different from what would typically be received from normal nondiabetic systemic circadian levels expected in normal rodents [21].…”
Section: Discussionmentioning
confidence: 99%